Fostering Early Numeracy through Natural Loose Parts: A Nature-Based Pedagogical Approach in Early Childhood Classrooms - Rosmayanti Rosmayanti; Irfan Fauzi Rahmat; Aip Syarifudin (Qualitative and Quantitative Research Center, 2026)
Early numeracy lays a critical foundation for abstract mathematical reasoning; however, conventional early childhood instruction frequently relies on abstract, worksheet-driven tasks that hinder active cognitive engagement. Framed by embodied cognition and constructivist theories, this practitioner action research evaluated the impact of a nature-based loose parts pedagogy, utilizing twigs, leaves, seeds, and stones, on early numeracy acquisition among 15 preschool children aged 4 to 5 years across two action cycles. Data were collected using validated observation rubrics, performance assessments, and video documentation. Results demonstrated substantial gains in developmental mastery, expanding from a baseline of 20.00% to 40.00% in Cycle I, and reaching 80.00% in Cycle II. Inferential verification confirmed that these gains were statistically significant (p < 0.001) with an exceptionally large effect size (r = 0.89). Granular analysis revealed that one-to-one correspondence achieved the highest growth trajectory, surging by +1.80 points on a 4-point scale (a 107.78% relative increase). Parallel improvements were recorded in teacher instructional facilitation (69.44% to 86.11%) and student active engagement (68.05% to 83.33%). Natural loose parts provided tactile-sensory scaffolding that mediated the cognitive transition from concrete physical manipulation to spatial-numerical mapping and symbolic abstraction. This research establishes nature-based loose parts pedagogy as an equitable, scalable, and low-cost early STEM intervention that bridges concrete tactile exploration with abstract mathematical reasoning.